Regulation of type 3 fimbria expression by RstA affects biofilm formation and virulence in Klebsiella pneumoniae ATCC43816 - Xiaoyun Zhang; Yaxuan Zhai; Jie Zhu; Zhichen Zhu; Yicheng Wen; Qizhao Gao; Liang Wang; Jiayao Lin; Yan Qian; Liang Chen; Hong Du (Microbiology Spectrum)
ABSTRACT Klebsiella pneumoniae causes both community-acquired and healthcare-associated infections, presenting a major therapeutic challenge to global public health. RstBA is a common two-component regulatory system that controls downstream gene expression in certain Enterobacteriaceae species. However, the role of RstBA in K. pneumoniae infection remains unknown. To determine its function, a wild-type K. pneumoniae strain (ATCC43816) and rstA mutant and complementation strains were constructed. Phenotypic experiments and in vivo animal infection assays demonstrated that deletion of rstA decreased virulence and biofilm formation. RNA sequencing analysis of ATCC43816 and rstA mutant strains was performed to study the regulatory mechanisms, revealing differential expression of genes involved in arginine and proline metabolism, phenylalanine metabolism, and quorum sensing. In addition, the mrkI and the mrkABCDF gene cluster, which regulates and encodes type 3 fimbriae, exhibited lower expression in the absence of rstA, possibly related to decreased virulence and biofilm formation. Quantitative real-time reverse transcription PCR, promoter activity assays, and electrophoretic mobility shift assays were conducted to identify the transcriptional regulation of mrkI and mrkABCDF by rstA. Our findings show that rstA regulates type 3 fimbriae expression by regulating mrkI indirectly and regulating mrkA directly by binding to its promoter. This study provides new insights into the functional importance of RstA in regulating biofilm formation and virulence in K. pneumoniae.IMPORTANCEKlebsiella pneumoniae is an opportunistic pathogen that has become a significant cause of community-acquired and nosocomial infections. The rise of hypervirulent and multi-drug-resistant K. pneumoniae poses a significant threat to public health. The two-component regulatory system is a typical signal-sensing and stress-response system widely distributed in bacteria, playing a critical regulatory role in bacterial infection. Through in vivo and in vitro experiments, we demonstrate that rstA regulates the expression of type 3 fimbriae by regulating mrkI indirectly and mrkA directly, thereby playing an essential role in the virulence and biofilm formation of K. pneumoniae. Understanding the regulatory mechanism of RstA in K. pneumoniae provides a proof-of-concept for identifying new genetic targets for controlling K. pneumoniae infection, which may aid in the development of therapeutic drugs.